IDENTIFIKASI KEMAMPUAN GURU DALAM MENGEMBANGKAN SOAL TES BERPIKIR KRITIS BERBASIS SDGs PADA IPA SD - Azizah, Tia Nur; Nugraha, Akhmad; Putri, Agnesrasia Ramadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Assessment by linking the issue of sustainable development as an effort to achieve the SDGs goals that have been designed and requires students to have skills in the 21st century. So teachers are required to be able to compose and develop critical thinking questions based on SDGs. The aim of this research is to identify teachers' abilities in developing SDGs-based critical thinking test questions in elementary schools and the causes. This type of research is qualitative. The main data source in the research includes fourth grade teachers at one of the elementary schools in Tasikmalaya City. The source of supporting data is documentation of written test questions. Interview and documentation data collection techniques. The instruments used in this research were interview guide sheets and documentation study guides. The technique used to analyze data is qualitative and quantitative descriptive analysis. The results of this research show that some teachers have created critical thinking test questions, but teachers have difficulty determining and determining the stimuli used in the test questions. Apart from that, teachers have not yet carried out SGDs-based evaluations. This is because teachers still do not know about the SDGs themselves. It can be concluded that there is a need for training and enforcement regarding SDGs for elementary school teachers because teachers' ability is still low to create critical thinking test questions based on SDGs